International Human Rights Law and Islamic Declarations of Human Rights: A Comparative Study - Bin Dehaish, Hesham AbdulMalik (Journal of Economic, Administrative and Legal Sciences, 2022)
This article will explain the mechanism by which it can be asserted that the language of human rights is compatible with Islamic law, as this article confirms that the language of human rights is compatible with Islamic law if it is used to implement Islamic principles and values. In other words, although Islamic law uses the language or method of duties to communicate its moral principles, the language of rights does not completely contradict them. According to Islamic law, there is no obligation to use the language of duties, as the important thing is to implement the provisions of Islamic law, whether through the language of rights or duties. Accordingly, human rights can be compatible with Islam provided that the starting point for its foundation is the religion itself and not the individual. In order to reach these results, this research follows the comparative analytical method, where the research analyzes the legal texts related to the topic of research in the two laws under study.